Graph Drawing in Motion - Friedrich, Carsten; Eades, Peter (Journal of Graph Algorithms and Applications, 2002)
Enabling the user of a graph drawing system to preserve the mentalmap between two different layouts of a graph is a major problem.In this paper we present methods that smoothly transform onedrawing of a graph into another without any restrictions to theclass of graphs or type of layout algorithm. <!---->